2012
DOI: 10.1260/2040-2295.3.4.621
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement in Hospitals: Identifying and Understanding Behaviors

Abstract: Improving operational performance in hospitals is complicated, particularly if process improvement requires complex behavioral changes. Using single-loop and double-loop learning theory as a foundation, the purpose of this research is to empirically uncover key improvement behaviors and the factors that may be associated with such behaviors in hospitals. A two-phased approach was taken to collect data regarding improvement behaviors and associated factors, and data analysis was conducted using methods proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Research has explored training, non-punitive cultures, and stakeholder inclusion in setting performance metrics (Nieva and Sorra, 2003;Hellings et al, 2010) as means to improve long-term organizational success, but these approaches largely focus on monolithic stakeholder groups, as opposed to individual behavioral change. Mazur et al (2012a) suggest a focus on behavioral change as a solution to long-term improvement and culture change. Their thesisbased on single-and double-loop learning theory (Argyris and Schon, 1978) argues that successful long-term improvement requires that each employee moves from a reactive quick fix mindset, in which they adhere to standard operating procedures (single-loop behavior), to one in which employees initiate problem-solving procedures to identify and eliminate root causes or identify and act on opportunities to improve normal operations (double-loop behavior).…”
Section: Introductionmentioning
confidence: 99%
“…Research has explored training, non-punitive cultures, and stakeholder inclusion in setting performance metrics (Nieva and Sorra, 2003;Hellings et al, 2010) as means to improve long-term organizational success, but these approaches largely focus on monolithic stakeholder groups, as opposed to individual behavioral change. Mazur et al (2012a) suggest a focus on behavioral change as a solution to long-term improvement and culture change. Their thesisbased on single-and double-loop learning theory (Argyris and Schon, 1978) argues that successful long-term improvement requires that each employee moves from a reactive quick fix mindset, in which they adhere to standard operating procedures (single-loop behavior), to one in which employees initiate problem-solving procedures to identify and eliminate root causes or identify and act on opportunities to improve normal operations (double-loop behavior).…”
Section: Introductionmentioning
confidence: 99%
“…
Figure 1 Consequences of suboptimal safety mindfulness during interactions with health information technology. 41 , 42
…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a safety-mindful mindset offers the opportunity to operate proactively (eg, something seems wrong here, this seems too perfect to be true) as opposed to reactively (eg, I assumed it was correct, I forgot to communicate), mitigated by using validated cognitive quality assurance (QA) routines and improvement behaviors. 41 , 42 , 43 …”
Section: Introductionmentioning
confidence: 99%
“…Although changing organizational culture is complex, evidence suggests that behavior change is still possible in organizations without fully supportive cultures. 4,5 Our first PDSA cycle involved interviewing those physicians who were considered to be "high performers" in our area of interest (ie, those with a low 90th percentile time from request to arrival) to identify improvement opportunities. Although certain process changes were suggested (eg, revisions to the physician call structure, having an additional physician overnight), it was also suggested that the team needed "good people who are eager to work" to make the process changes successful.…”
mentioning
confidence: 99%
“…This combination of process and behavioral changes is noteworthy, as it is known that if process improvements require behavioral changes, performance improvement in hospitals is complex. 4 Physicians, in particular, are a challenging group to influence behaviorally because they have been trained as autonomous providers and, in Canada, are not employees of the organization. 6,7 Hence, it is paramount to the success of QI to assess whether the improvement relies solely on process change or requires behavioral change, as the latter requires different supports and project team structure than the current project.…”
mentioning
confidence: 99%